PROSES LITERASI STATISTIKA CALON GURU MATEMATIKA DITINJAU DARI PENGETAHUAN AWAL - Gunawan, Gunawan; Purwanto, Joko; Subekti, Fitrianto Eko; Rizki, Swaditya (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
Literacy skills are important for prospective mathematics teachers in 21st century education, especially in the field of statistics. The purpose of the research was to describe the statistical literacy process based on initial knowledge. The subjects of the study were 50 students of Mathematics Education at the Universitas Muhammadiyah Metro Lampung and the Universitas Muhammadiyah Purwokerto. The research applies a descriptive qualitative method. Data collection used literacy test instruments and in-depth interview guidelines. Based on the results of previous knowledge tests, subjects were grouped into three categories of high, medium, and low. Each category was taken by one person as an informant with purposive sampling techniques. The data analysis technique is carried out with the stages of data reduction, presentation, and final conclusion. The mathematical literacy process includes the stages of data orientation, data processing, and data interpretation. The results of the study prove that students in the early and medium knowledge categories are able to detail activities at the stages of data orientation, processing, and interpretation. Identifying information and main problems is the key for the student to process the data. At the end of the answer, the student is in the high category and is giving a final conclusion and examination of the answer. In contrast to students in the low initial knowledge category, mistakes made in data orientation resulted in errors in applying mathematical concepts. Thus, the process stage and interpretation of data cannot be fulfilled correctly. The results of the study have a positive impact on the mathematical thinking process to solve contextual problems.